2019
DOI: 10.1021/acsami.9b07965
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Loudspeaker Effect of Graphene-Based Hybrid Material To Improve Low-Frequency Acoustic Performance

Abstract: Closed-box loudspeaker systems (CBLSSs) are compact and simple air-suspension loudspeaker systems, and their low-frequency responses are determined by two fundamental parameters: resonance frequency and total damping. Recently, electronic devices have come to require more compact designs, so the volumes of loudspeaker should be reduced. However, a small loudspeaker cannot retain sufficient acoustic space, resulting in poor low-frequency acoustic performance. Herein, we investigated acoustic characterization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Despite their equal thickness (25 μm), the total SPL of the flat PI and three PIs with different micropatterns showed a difference of up to 15 dBA. It is determined that the above results shown by the change in the maximum displacement and resonant frequency change according to eqs –, and they are consistent with the change in thickness and mass reduction compared to the flat PI case. We calculated the Eigen mode of different diaphragms with/without micropatterns by referring ,, to the method in which the maximum displacement is determined according to the Eigen mode and frequency of the thin actuator, and thus, the maximum sound pressure level is generated. Comparing Figure b–f and Table S-2, it can be confirmed that the natural frequency and the maximum displacement of the thin film according to mode 1 (0,1) are consistent with the actual experimental values.…”
Section: Resultsmentioning
confidence: 69%
“…Despite their equal thickness (25 μm), the total SPL of the flat PI and three PIs with different micropatterns showed a difference of up to 15 dBA. It is determined that the above results shown by the change in the maximum displacement and resonant frequency change according to eqs –, and they are consistent with the change in thickness and mass reduction compared to the flat PI case. We calculated the Eigen mode of different diaphragms with/without micropatterns by referring ,, to the method in which the maximum displacement is determined according to the Eigen mode and frequency of the thin actuator, and thus, the maximum sound pressure level is generated. Comparing Figure b–f and Table S-2, it can be confirmed that the natural frequency and the maximum displacement of the thin film according to mode 1 (0,1) are consistent with the actual experimental values.…”
Section: Resultsmentioning
confidence: 69%
“…To explore the acoustic effects of ZSM-5 GR-cal as a filling material, a platform was set up for evaluating the low frequency of a 1.0 cm 3 enclosed-box microloudspeaker with either empty or filled with filling materials (Figure S6). The vibrational characteristics of a microloudspeaker, modeled as a mass-spring system with a moving mass (speak unit) and an acoustic spring, contributed by the air inside the enclosure, are affected by total stiffness consisting of unit stiffness from vibration components and acoustic spring stiffness. ,, Generally, in terms of vibration and acoustic analysis, the unit stiffness and added stiffness act in parallel on the vibration system . Since a microloudspeaker is driven by Lorentz force that is affected by the induced electromotive force (back emf), the acoustic vibration characteristics of the entire system can be described by the magnitude of the electrical impedance.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The growing demand for microloudspeakers in slim cellular phones, laptops, earphones, and other flexible devices has fueled the search for high-performance, sustainable acoustic materials. Toward this aim, zeolites have emerged due to their unique adjustable micropores, high specific surface area, high gas adsorption, and storage properties, demonstrating significant application potential as acoustic filling materials for improving the low-frequency performance in the enclosure of closed-box microloudspeakers with an air-suspension system. This strategy enables a small system that has the same low-frequency response as a large system, increasing the acoustic volume of miniature multimedia devices with audio output as well as extending the frequency output range. Recently, researchers have revealed that porous structures support the mass transfer in sorption and diffusion processes, in addition to the usual visco-thermo-inertial interactions. , Micropores have been confirmed to exhibit pressure diffusion effects, subsequently bringing dissipation when sound waves propagate in porous media . Additionally, it has also been demonstrated that sorption effects occurring in nanosized pores drastically modify the macroscopic mass balance, leading to slower speed sound and higher sound attenuation in the materials .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kim et al filled the closed-box loudspeaker systems (CBLSSs) with thermally expanded GO (TEGO) in melamine foam. 137 Due to the high adsorption and the thermal properties of TEGO, the low-frequency performance of CBLSSs was greatly improved. Similarly, Shin et al enclosed the CNT film into a cavity covered by a vibrating plate.…”
Section: Challenge and Prospectmentioning
confidence: 99%